Extremely obese children respond better than extremely obese adolescents to lifestyle interventions. Issue 1 (17th December 2013) - Knop, C.; Singer, V.; Uysal, Y.; Schaefer, A.; Wolters, B.; Reinehr, T.
Summary What is already known about this subject Lifestyle intervention is regarded as therapy of choice in obese children and adolescents. It is unclear whether extremely obese children and adolescents respond to lifestyle intervention. What this study adds Extremely obese children respond better than obese children to a lifestyle intervention. In contrast, most extremely obese adolescents achieved no weight loss in lifestyle intervention suggesting that other treatment approaches are needed for them. Background There are conflicting results of treating extreme obesity in childhood by lifestyle interventions in the literature. Methods We analysed the outcome of a 1‐year lifestyle intervention in an intention‐to‐treat approach in 1291 children (mean age 11.0 ± 2.5 years, mean body mass index [BMI] 27.5 ± 4.7 kg m−2, 55.8% female, 62.4% obese, 37.6% extremely obese (defined by BMI‐SDS >2.3) at end of intervention and 1 year later. Results The mean BMI‐SDS reduction was −0.20 ± 0.32 at end of intervention and −0.14 ± 0.37 1 year after end of intervention compared to baseline (comparing intervention vs. 1 year later P = 0.010). Extremely obese children ≤10 years demonstrated a significantly greater BMI‐SDS reduction than obese children ≤10 years (−0.24 ± 0.38 vs. −0.16 ± 0.38, P = 0.021). Extremely obese adolescents >10 years demonstrated a significantly lower BMI‐SDS reduction compared to obese adolescents >10 years (−0.05 ± 0.30 vs. −0.15 ± 0.39, P < 0.001). Comparing the BMI‐SDS reduction between obese children <10 years and >10 years revealed no significant difference (P = 0.195) in contrast to the comparison between extremely obese children <10 years and >10 years (P < 0.001). The same findings were observed in the follow‐up period after the end of intervention. Conclusions Our study demonstrated an encouraging effect of lifestyle intervention in extremely obese children ≤10 years at the end of intervention and 1 year later, but only a limited effect in extremely obese adolescents >10 years.